Strategi Medical Tourism Thailand Dalam Mewujudkan Branding Negaranya Sebagai “Thailand As A World Class Health Care Provider” Pada Tahun 2014-2018 Di Dunia Internasional (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
Thailand is one of the countries with great potential in the medical tourism sector. From 2003 to 2008 the Thai government had a program to increase its medical tourism entitled “Thailand: The Excellent Medical Hub of Asia”. From 2008 to 2014 the Thai government did not include medical tourism on its government agenda, where in 2014 there was a decline in the arrival of foreign patients. The Thai government seeks to maximize the sector by creating branding for its country as “Thailand As A World Class Health Care Provider” from 2014 to 2018. To realize the country's branding, the Thai government implemented a branding strategy, namely the promotion of Thai medical tourism through the application of minimum prices, the Thai government's visa policy, and the development of Thai medical facilities and services. Keywords : medical tourism, nation branding, strategy, Thailand